2021
DOI: 10.1111/dme.14671
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional longitudinal association between depressive symptoms and HbA1c: A systematic review and meta‐analysis

Abstract: Aim To investigate whether there is a bidirectional longitudinal association of depression with HbA1c. Methods We conducted a systematic literature search in PubMed, PsycINFO, CINAHL and EMBASE for observational, longitudinal studies published from January 2000 to September 2020, assessing the association between depression and HbA1c in adults. We assessed study quality with the Newcastle‐Ottawa‐Scale. Pooled effect estimates were reported as partial correlation coefficients (rp) or odds ratios (OR). Results W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Another possibility explaining the association between hyperglycemia and LLD is its involvement via generalized MVD [ 79 ] and inflammation [ 113 ], which both may lead to CSVD [ 114 ], and subsequent depression [ 79 , 115 ]. Several meta-analyses have examined the role of hyperglycemia in the etiology of LLD and found evidence that continuous hyperglycemia levels may be involved in the development of depression [ 116 ], which is in line with a large cross-sectional study demonstrating the association between diabetes and higher prevalence of depression [ 117 ]. In conclusion, there is evidence for many metabolic factors, including hyperglycemia, obesity, and type 2 diabetes as important metabolic risk factors in LLD.…”
Section: Metabolic Risk Factorsmentioning
confidence: 62%
“…Another possibility explaining the association between hyperglycemia and LLD is its involvement via generalized MVD [ 79 ] and inflammation [ 113 ], which both may lead to CSVD [ 114 ], and subsequent depression [ 79 , 115 ]. Several meta-analyses have examined the role of hyperglycemia in the etiology of LLD and found evidence that continuous hyperglycemia levels may be involved in the development of depression [ 116 ], which is in line with a large cross-sectional study demonstrating the association between diabetes and higher prevalence of depression [ 117 ]. In conclusion, there is evidence for many metabolic factors, including hyperglycemia, obesity, and type 2 diabetes as important metabolic risk factors in LLD.…”
Section: Metabolic Risk Factorsmentioning
confidence: 62%
“…The results of a recent meta-analysis of longitudinal studies indicate that the baseline level of depression is much more associated with the risk of increased levels of glycated hemoglobin (HbA1c) than vice versa. 3 The results for other psychological and social factors are not as well documented. Two large international studies Diabetes, Attitudes, Wishes and Needs (DAWN) 4 and the Second DAWN study/DAWN2 5 did not take into consideration a level of HbA1c, that reflects the average blood glucose concentration at approximately 3 months before the test, with the majority (about 60%) of HbA1c being formed in the last month before the test.…”
Section: Introductionmentioning
confidence: 98%
“…There is a large body of research that has demonstrated that mental ill-health among people with diabetes increases changes of an unhealthy lifestyle [11], cardiovascular complications [12], and all-cause mortality [13]. Associations between mental ill-health and glycated haemoglobin (HbA 1c ) seem bi-directional: depressive symptoms have been associated with developing suboptimal HbA1c, and suboptimal HbA1c has been associated with an increased risk of developing depression [14].…”
Section: Introductionmentioning
confidence: 99%